Memoirs of a sidekick - Skuy, David, 1963- (Kids Can Press Ltd., 2016)
When Boris Snodbuckle decides to run for student council president, his best friend and number-one sidekick Adrian is there to help him out. But with an opponent who's an ultra-popular bully and cheat, Boris and Adrian might be in over their heads.